Impact of a trained vascular access coordinator on a vascular access program in India. Issue 4 (July 2022) - Pundir, Ekta; Sharma, Ashish; Singh, Sarbpreet; Patil, Shivakumar; Pandey, Gaurav Shankar; Rally, Sahil; Kenwar, Deepesh Benjamin
Background: Native AV fistulas are the ideal access for hemodialysis but require monitoring and multiple interventions in some patients to keep them functioning. The aim of the study was to assess the impact of the appointment of a trained vascular access coordinator (VAC) for fistula monitoring, on the evolution of the vascular access program at our institute. Method: Data was retrieved from the departmental database for the baseline year 2014 and compared with the data from 2018. Initial review showed that appointment of the VAC in 2015 resulted in a steady increase in the number of AV fistula interventions over 2 years to a plateau in 2018 which was chosen as the comparison year. The number of AVF's created, number of salvage procedures performed, and follow-up data were compared. Other parameters like number of operation theatre hours, surgeons, and nursing staff remained constant during this period. Result: Total numbers of AVFs increased from 511 to 713 (39.3%). The number of follow-up visits to surgeons reduced from an average of 4–0.25 visits per patient during this period. Follow up Doppler examinations increased from 761 to 1296 (70%) indicating improved follow up. The salvage procedures increased from 44 to 161 (272%) with early detection of fistula dysfunction. Primary and secondary patency rates of 86% and 92% at 3 months could be achieved whereas limited follow-up data was available for 2014. Conclusion: Appointment of trained VAC increased the number of vascular access procedures, improved follow-up care, and led to early detection and intervention for access dysfunction while reducing the workload of surgeons.